One Health and a Computational Biology approach (Research, Society and Development, 2022)
The current concept of One Health is based on the union of three inseparable pillars: human, animal, and environmental health, principles that must be paramount in any project or action in a society. The holistic view becomes fundamental to ensure levels of excellence in the health area as a whole, in addition to numerous diseases and pathologies being prevented and combated through the integrated action of professionals in these three areas. Nevertheless, One Health emerges as a worldwide concept and several projects are being based on this common good practice integrated with the most prominent technologies today, such as computational biology. In this way, national measures and laws are also being amended in pursuit of the principle being based on all places and situations that need to use environmental or animal resources for any circumstance. The primary objective of this brief literature review is to exemplify the concept of the One Health approach based on articles that applied the concept practically, with emphasis on prophylactic measures, applications in bioinformatics, and results presented with this well-known foundation.